Accelerating machine learning using risc-v vector extension in a manycore platform - Nunes, Willian Analdo (2025)
The increasing computational demands of Machine Learning (ML) workloads, particularly Convolutional Neural Networks (CNNs), require efficient hardware acceleration solutions. This dissertation investigates the RISC-V Vector Extension (RVV) to accelerate the CNN inference in single-core and manycore architectures. The research presents the RS5 processor, an RTL implementation of a RISC-V-based core enhanced with a subset of RVV instructions designed for efficient data parallelism. Additionally, this processor was integrated into the Memphis-V manycore platform, enabling further performance scaling through parallel execution. A comprehensive evaluation was conducted to analyze the impact of RVV-based acceleration on performance, energy consumption, memory footprint, and hardware área costs. The results demonstrate that the vectorized implementation of CNN operations on the RS5 processor achieves a speedup of up to 7.68x (1-D CNN layer) in single-core execution compared to a scalar baseline, reducing energy consumption by up to 61% and achieves speed-ups of up to 16x in a dot-product application. When deployed in the manycore environment, additional performance gains were observed, with the first layer of AlexNet achieving up to 5.7× acceleration over the scalar single-core implementation and reducing code size by up to 87% in the second layer. The integration of auto-vectorization and manually optimized vector assembly further highlighted the effectiveness of RVV in accelerating ML workloads. Experimental results demonstrate that the integration of RVV significantly enhances CNN inference speed. The manycore implementation further amplifies these benefits, highlighting the potential of RISC-V-based vector architectures for efficient ML acceleration. This work contributes to hardware acceleration by showcasing a scalable, open-source solution for CNN applications.